Working with big data as indicators of socio-ecological-economic development - Шаховська, Наталя Богданівна; Болюбаш, Юрій Ярославович (Eastern-European Journal of Enterprise Technologies, 2013)
The paper considers the features of socio-ecological and socio-economic data analysis and indicates that they should be processed as Big data. The features of data consolidation process and arising problems are mentioned. The main problems arising during the data processing are the lack of analysis methods suitable for use due to their variety (regional numerical data and geodata, semi-structured reports, etc.), the need for human resources for supporting the data analysis process, high computational complexity of available analysis algorithms and rapid growth of collected data. Information technology was defined for working with regional data. The scheme of data warehouse was designed and the method for predicting the values of regional indicators was selected. Prediction of region development is realized by the time series method based on analysis of previous states of region. Verification of data homogeneity was carried out on the basis of the Irwin criteria. The most appropriate technology for working with regional Big data is data space. Logical model of regional data was designed.